Answers

Wow, thank you so much explaining this to me!

15 September 2016

See Jonas' solution for the correct way to solve the problem, where we consider the energy transfer from gravitational potential energy to kinetic energy. Just to show the algebra:gravitational potential energy = mgh, kinetic energy = ½mv²mgh = ½mv²m cancels from both sides: gh = ½v²rearrange to find the speed v: 2gh = v² ⇒ v = √(2gh)

23 September 2016

use the acceleration of gravity (g)and suvathope that helped.

07 October 2016

Add an answer